The policy process model and the systems model in monarchy: The case of the United Kingdom and Saudi Arabia - Yu Andrew (De Gruyter, 2020)
By taking two monarchy countries as examples, this paper discusses the differences and similarities of the policy process model and the systems model. The difference has first been discussed. Policies in the United Kingdom can be applied to the policy process model, due to the fact that step-by-step policymaking procedures can be observed during the policymaking process in the United Kingdom. The case shows that policies made by countries with democracy can also be analyzed by using the policy process model. On the contrary, policies in Saudi Arabia can be studied by using the systems model, due to the fact that unclear policymaking procedures can be witnessed in Saudi Arabia. This paper also discusses two similarities between the two models. They both emphasize on “policy cycle”, as well as influenced by different kinds of environment. While social policy is always influenced by political ideology and system, and can be studied by different models, this paper concludes that the policymaking process is, all in all, a cycle and can be influenced by different environmental factors, no matter what political system a country has.